Atypical spindle cell osteosarcoma in the diaphysis and proximal epiphysis of the tibia: clinical case report (Revista de Investigaciones Universidad del Quindío, 2023)
Osteosarcoma is the most common primary malignant tumor of the bone, characterized by the formation of osteoid from tumor cells. Its most common location is in the metaphysis of the long bones; however, the proximal part of the tibia is one of the most frequent, with 50% to 60% of cases. The aim of this work is to describe a case study of a male patient diagnosed with spindle cell osteosarcoma, who presented signs and symptoms three months prior to evaluation, secondary to localized trauma to his lower limb. From the imaging point of view, an image suggestive of a metaphyseal tumor lesion that extended to the epiphysis and the medullary canal was observed. The histopathological and imaging study concluded that the patient had a grade II spindle cell osteosarcoma in the right proximal tibia, which required surgical management and chemotherapy with a good clinical response. The importance of scientific and biomedical advances is evident, which have allowed a better management of these diseases and a treatment that generates better conditions for post-surgical rehabilitation and life expectancy.
Keywords: neoplasia; sarcoma; diaphysis; epiphysis